2016
DOI: 10.3390/microorganisms4020020
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome, Metabolome and Inflammatory Bowel Disease

Abstract: Inflammatory Bowel Disease (IBD) is a multifactorial disorder that conceptually occurs as a result of altered immune responses to commensal and/or pathogenic gut microbes in individuals most susceptible to the disease. During Crohn’s Disease (CD) or Ulcerative Colitis (UC), two components of the human IBD, distinct stages define the disease onset, severity, progression and remission. Epigenetic, environmental (microbiome, metabolome) and nutritional factors are important in IBD pathogenesis. While the dysbioti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
136
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(151 citation statements)
references
References 164 publications
5
136
0
1
Order By: Relevance
“…Prebiotics are also speculated to protect the gut epithelium by increasing the mucus layer, elongating the microvilli, increasing numbers of epithelial cells, and by preventing adherence of pathogenic strains to the epithelial cells . Other SCFAs such as propionate appear to induce de novo generation of T regs in the peripheral immune system . A newly published study in mice revealed that when deprived of fiber, commensal bacteria will degrade the protective mucosal mucus layer, permitting invasion by commensals and pathogens alike …”
Section: Therapeutic Manipulation Of the Gastrointestinal Microbiomementioning
confidence: 99%
“…Prebiotics are also speculated to protect the gut epithelium by increasing the mucus layer, elongating the microvilli, increasing numbers of epithelial cells, and by preventing adherence of pathogenic strains to the epithelial cells . Other SCFAs such as propionate appear to induce de novo generation of T regs in the peripheral immune system . A newly published study in mice revealed that when deprived of fiber, commensal bacteria will degrade the protective mucosal mucus layer, permitting invasion by commensals and pathogens alike …”
Section: Therapeutic Manipulation Of the Gastrointestinal Microbiomementioning
confidence: 99%
“…4,5 Accumulating evidence suggests that the well-known enterotoxigenic Escherichia coli (ETEC) causes a high rate of intestinal disorders and diarrhea in newborns and young animals. 7,8 The intestinal barrier formed by the intestinal epithelium and its tight junction (TJ) proteins (TJPs), including zonula occludens (ZO), occluding, and claudins, provides a physical barrier that blocks the entry of pathogens into the lamina propria and protects against the invasion of enteropathogenic microorganisms. 7,8 The intestinal barrier formed by the intestinal epithelium and its tight junction (TJ) proteins (TJPs), including zonula occludens (ZO), occluding, and claudins, provides a physical barrier that blocks the entry of pathogens into the lamina propria and protects against the invasion of enteropathogenic microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the most widely studied system is the gut microbiome due to its critical role in food metabolism [26][27][28], profound influence on the immune system [29,30] and suspected role in a wide variety of diseases including gut infections [31], inflammatory bowel and Crohn's diseases [32,33], obesity [34], diabetes [35], cardiovascular disease [36], rheumatoid arthritis [37], colorectal cancer [38] and even depression [39]. The human gut microbiome is a highly complex multispecies system thought to consist of at approximately 1800 genera and 15,000-36,000 species of microbes [40].…”
Section: Introductionmentioning
confidence: 99%